Assessment of hydrological and landscape controls on gully formation and upland erosion near Lake Tana - Zegeye, Assefa D.; Tebebu, Tigist Y.; Abiy, A. Z.; Dahlke, H. E.; White, E.D.; Collick, A.S.; Kidnau, S.; Dadgari, F.; McCartney, Matthew P.; Steenhuis, Tammo S. (2009)
Gully formation and upland erosion were studied in the Debre-Mewi Watershed in the Gilgil Abay Basin south of Lake Tana. Gully erosion rates were found to be equivalent to over 500 tonnes/ha/year for the 2008 rainy season when averaged over the contributing watershed. Upland erosion rates were twentyfold less. Gully formation is accelerated when the soils are saturated with water as indicated by water table readings above bottom of the gully. Similarly, upland erosion was accelerated when the fields were close to saturation during the occurrence of a rainfall event. Height of the water table is an important parameter determining the amount of erosion and should, therefore, be included in simulation models.